The phantom syndrome: a descriptive study on prevalence and association with smartphone addiction and perceived stress among medical students in central Kerala - Sebastian, Shaliet Rose; Saji, Joyal Alias; Salam, Sujaid Abdul; Victor, Jibin Joshua; Puthuvana, Ashish Thomas (International Journal Of Community Medicine And Public Health, 2020)
Background: Technology in Communication has developed drastically in recent years and the introduction of smartphone is a crucial milestone in history. The constant involvement of people with their smartphone has led to the surfacing of a new kind of psychological disorder called as the phantom syndrome, comprising of phantom vibration syndrome (PVS) and phantom ringing syndrome (PRS), characterized by a recurrent false sensation of vibration and ringing from their smartphones. Methods: A cross sectional study was conducted among Four hundred eighty seven medical students in Thiruvalla Taluk of Pathanamthitta District, Kerala to estimate prevalence of such sensations among medical students and their association with perceived stress levels and smartphone addiction. Data was collected using a semi structured questionnaire for details about the phantom vibration/phantom ringing sensations over the last 1-month, perceived stress scale (PSS), smartphone addiction scale short version (SAS SV). Chi-square test and odds ratio with 95% confidence interval were used to evaluate statistical significance of association. Results: 59.1% have a sensation of phantom vibration and 61% experienced phantom ringing syndrome. 73.5% students perceived stress and 67.6% had smartphone addiction. Phantom vibration and phantom ringing were significantly associated to perceived stress and smartphone addiction. Conclusions: This study throws light on the stress levels and excessive smartphone use among medical students, and the association of smartphone phantom sensations with smartphone addiction and stress level.